Using the UTAUT model to analyze user intention to accept electronic payment systems in Serbia - Tomić, Nenad (2023)
This study applies The Unified Theory of Acceptance and Use of Technology (UTAUT) to explain the acceptance of electronic payment systems in Serbia. We used extended model that incorporates several external variables, such as perceived security, trust, privacy, convertibility and financial costs, along with basic UTAUT predictors. The sample comprised of 457 respondents. We applied structural equation modelling to develop the model and draw conclusions. The results showed that performance expectancy, perceived security, trust and social influence had strong positive effects on behavioral intention. Conversely, we found behavioral intention, convertibility and financial costs to be significant drivers of user behavior. We consider the inclusion of convertibility in the model and proving its significance to be the main practical implications of our research, and also suggest to be considered as a factor in models designed for countries with low purchasing power of national currency.